A time-resolved fluorescence microsphere-lateral flow immunochromatographic strip for quantitative detection of Pregnanediol-3-glucuronide in urine samples - Lin, Jiasheng; Li, Sanhua; Ye, Benchen; Zheng, Weigang; Wang, Huihui; Liu, Ying; Wang, Dong; Wu, Zaihui; Dong, Wen-Fei; Zan, Minghui (Frontiers in Bioengineering and Biotechnology, 2023)
Pregnanediol-3-glucuronide (PdG), as the main metabolite of progesterone in urine, plays a significant role in the prediction of ovulation, threatened abortion, and menstrual cycle maintenance. To achieve a rapid and sensitive assay, we have designed a competitive model-based time-resolved fluorescence microsphere-lateral flow immunochromatography (TRFM-LFIA) strip. Inspiringly, the optimized TRFM-LFIA strip exhibited a wonderful response to PdG over the range of 30−2000 ng/mL, the corresponding limit of detection (LOD) was calculated as low as 8.39 ng/mL. More importantly, the TRFM-LFIA strip was innovatively used for the quantitative detection of PdG in urine sample, and excellent recovery results were also obtained, ranging from 97.39−112.64%. Therefore, the TRFM-LFIA strip possessed robust sensitivity and selectivity in the determination of PdG, indicating the great potential of being powerful tools in the biomedical and diagnosis region.